2019
DOI: 10.2147/ijn.s205295
|View full text |Cite
|
Sign up to set email alerts
|

<p>Enhanced transdermal delivery of lornoxicam by nanostructured lipid carrier gels modified with polyarginine peptide for treatment of carrageenan-induced rat paw edema</p>

Abstract: Background: Nanostructured lipid carriers (NLCs) are emerging as attractive drug carriers in transdermal drug delivery. The surface modification of NLCs with cell-penetrating peptides (CPPs) can enhance the skin permeation of drugs. Purpose: The objective of the current study was to evaluate the ability of the cell-penetrating peptide (CPP) polyarginine to translocate NLCs loaded with lornoxicam (LN) into the skin layers and to evaluate its anti-inflammatory effect. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 56 publications
2
13
0
Order By: Relevance
“…47 Studies have shown that nanoscale drugs were taken up to a greater extent than free drugs. 48,49 In our uptake study, BBR-NLCs showed superior uptake compared with free BBR (Figures 1 and 5). In addition, qualitative analysis of uptake in vitro showed that BBR was distributed in the cytoplasm and nucleus, which was consistent with the findings of a study by Serafim.…”
Section: Discussionmentioning
confidence: 63%
“…47 Studies have shown that nanoscale drugs were taken up to a greater extent than free drugs. 48,49 In our uptake study, BBR-NLCs showed superior uptake compared with free BBR (Figures 1 and 5). In addition, qualitative analysis of uptake in vitro showed that BBR was distributed in the cytoplasm and nucleus, which was consistent with the findings of a study by Serafim.…”
Section: Discussionmentioning
confidence: 63%
“…Topical application of drug loaded gel (containing Transcutol P as permeation enhancer) with and without microneedles followed the concentration pattern, with higher drug concentration, higher was the efficacy. Furthermore, the results also clearly indicated that the use of microneedle significantly improved the effectiveness of drug loaded gel at the dose of 0.05 mL from 43% to 51% (p < 0.01) and at the dose of 0.1 mL from 65% to 72% ( Wang et al, 2017 , Gao et al, 2019 ). This enhancement was attributed to the disturbance of stratum corneum with microneedles, which allowed drug molecules to rapidly permeate the skin and resulted in quick therapeutic effect ( Al-Mayahy et al, 2019 ).…”
Section: Resultsmentioning
confidence: 78%
“…Gao et al prepared lornoxicam-loaded lipid gels by R11 modified (LN-NLC-R11) to treat rat paw edema. LN-NLC-R11 significantly improved cellular uptake of NLC in HaCaT cells, remitted rat paw edema, and inhibited the inflammatory cytokines production than NLC in vivo (Gao et al, 2019). Due to steric hindrance, the distance between CPPs and nanoparticles will influence the efficiency of cellular internalization.…”
Section: Application Of Cpps In Inflammationmentioning
confidence: 99%